Plan de marketing para el posicionamiento del emprendimiento Shoes Milen, en el cantón San Miguel, período 2023-2027 - Cornelio Tibanlombo, Yuliana Maribel (2024)
The present research work was prepared with the main objective of developing a marketing plan for the positioning of the entrepreneurship Shoes Milen in the city San Miguel, for this purpose the specific objectives were set to theoretically substantiate the topic, carry out a current situational analysis and propose marketing strategies. The enterprise in which the research was carried out does not currently have a marketing plan, nor does it use social networks to promote its products, which causes it to not obtain recognition. For this, the research was based on a descriptive field design, working with a sample population of 71 consumers, to collect the information, surveys were used which were applied through questionnaires to the clients and an interview was applied to the owner. Study matrices were also carried out such as: internal factors matrix, profile matrix, weighting matrix, FODA matrix, PESTEL matrix and Michael Porter's five forces which allowed the analysis of the internal and external factors of the business. The marketing plan proposal is based on the development of strategies which help solve the needs of the enterprise and strengthen them by using social networks to promote their products. It is recommended that each of the strategies be taken into account since they are developed for the benefit of the enterprise to achieve the proposed objectives.